Design and development of nanocosmeceutical containing natural antioxidant from Manilkara zapota (L.) P. Royen fruit extract - Shafii, Ziti Akhtar (2017)
Plant-based extract is gaining interest as natural antioxidant in cosmetic industry. However, the primary challenges are incorporation of plant-based extract due to its poor bioavailability, low solubility and difficulties in formulating a stable carrier system. A newly developed nanoemulsion with extremely small particle size system was designed and formulated for transdermal application. To date, there are no reports on the uses of natural antioxidants from Manilkara zapota (L.) P Royen for topical applications in cosmeceuticals. Polyphenolic compounds (phenolic acid, flavonoid and tannin) are the major contributor to the antioxidant properties of M.zapota fruits. Polyphenolic compounds in M.zapota fruit were extracted and evaluated. In-vitro antioxidants activity were evaluated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging, ß-carotene bleaching assay and oxygen radical absorbance capacity (ORAC). The highest antioxidant properties was observed in ethanol pulp (EtPE), ethyl acetate pulp (EaPE) and ethyl acetate seed (EaSE) extracts of M.zapota. The bioactive compounds were analyzed by Liquid Chromatography Mass Spectroscopy (LCMS) and Gas Chromatography Mass Spectroscopy (GCMS). The results demonstrated the presence of gallic acid, protocatachuic acid, ferullic acid, resorcinol, vanillic acid, epicatechin, quercetin linoleic acid and oleic acid in EtPE, EaPE and EaSE extracts. Palm kernel oil esters (PKOEs), date seed oil (DSO) with addition of sorbitan monooleate (Span 80) and polyoxyethelene sorbitan monooleate (Tween 80) were chosen to be used as the oil phase due to high solubility of M.zapota fruit extract. In order to determine the suitable ratio of mixed surfactant, ternary phase diagram was constructed. Ternary phase diagrams were constructed to observe the incorporation of mixed palm kernel oil esters (PKOEs) and date seed oil (DSO), non-ionic surfactants, active compound and water. A composition of surfactant/oil/water (20/20/60) in ternary phase diagram was chosen and the particle size was measured. The results showed that the ratio of Span 80 to Tween 80 (3:7) exhibited the lowest particle size and polydispersity index. The formulations were optimized using a multivariate statistical techniques by D-optimal experimental mixture design with oil, surfactant, xanthan gum, glycerol, water as the variables and particles size as the response. The nanoemulsions were prepared using high energy emulsification followed by low energy emulsification method. The optimum compositions were 14.03% (w/w) of oils, 7.86% (w/w) of surfactants, 0.64% (w/w) of xanthan gum, 7.35% (w/w) of glycerol, and 70.12% (w/w) of water. The particle size, zeta potential, and polydispersity index (PDI) obtained were 112.24 nm, -42.11 mV, and 0.3254, respectively. The surfactant amount gave the largest effect on the particle size of the system. In order to prepare a good texture which fits for cosmetic purpose, modifications was carried out. The modification made did not show any significant changes on the particle size and zeta potential readings. The final formulations contained 0.0%, 0.1% and 0.5% of M.zapota fruit extract were labeled as BNE, MZNE1 and MZNE2. The particle sizes obtained were 110.0, 121.7 and 123.9 nm, respectively. The results showed that final nanoemulsions were stable up to 90 days in storage (room temperature (25°C, 45°C and 5°C). There were no bacterial growths in the storage. In-vitro safety evaluation of nanoemulsions showed no acute toxicity on fibroblast cells (3T3) up to 48 hours. Rheological behavior of nanoemulsion was evaluated using viscometry test. From the results, nanoemulsion exhibited shear thinning (pseudoplasic) behavior which obeys the power law model. The results from oscillatory strain sweep test showed that the wide linear viscoelastic region (LVR) was directly correlated to high rigidity of the system. The morphological property of the nanoemulsion analysed using Transmission Electron Microscope (TEM) showed that the particle size was in agreement with the sample measured size using Zeta Sizer Analyzer. In the physical and thermal stability studies, the nanoemulsion was stable under high centrifugal force, storage at room temperature and 45°C for 90 days while maintaining its nano-size and zeta potential values. The developed nanoemulsion was also able to withstand freeze-thaw cycles and having low rate of Ostwald ripening. The permeation of phenolic compounds through cellulose acetate membrane was studied using Franz diffusion cells. The result showed that 39.44% of total phenolic compounds were released from MZNE2. The antioxidant activity released was evaluated by DPPH scavenging assay. The activity were 29.94%, 27.81%, 48.25% and 68.64% of MZFE, BNE, MZNE1 and MZNE2, respectively. The nanoemulsions system provided a good protection for bioactive polyphenol compounds against degradation as there was significant antioxidant activity even after being encapsulated in the system. The biophysical evaluations of MZNE2 on skin hydration showed significantly increased for 6h treatment. However the collagen content showed significant increase after 28d of application compared to 6h application. Transepidermal water loss was reduced in both treatments of 6h and 28d of applications. In addition, MZNE2 was classified as dermally non-irritant with a Human Irritancy Equivalent (HIE) score below 0.19 and this has been verified by the ultrasound skin imaging after application. No visible skin reactions caused by dermal irritation, contact sensitization or rash were experienced by the subjects during the application. The in vivo study has demonstrated that the increase of collagen content eventually led to higher skin hydration. This work conclude that a stable M.zapota nanoemulsion was successfully designed and developed, and showed potential collagen regeneration and delay intrinsic and extrinsic skin aging on human skin.